Efektivitas Komunikasi Pemasaran pada Usaha Kecil Menengah (UKM) di Kabupaten Bandung - Asep Suryana (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2001)
The objectives of the study were: (1) To know the dynamics of Small and middle Scale Industry (SMSI) in Kabupaten Bandun; (2) Individual effectivity on SMSI in KabupatenBandung; (3) Marketing communication management effectivity on SMSI in Kabupaten Bandung; (4) The correlation between organization dynamics level and individual effectivity on SMSI organization in Kabupaten Bandung; (5) The correlation between organization dynamics level and effectivity of marketing communication management on SMSI in Kabupaten Bandung; and (6) The correlation between individual effectivity level and effectivity of marketing communication management on SMSI in Kabupaten Bandung. The methodology used in this study was Survey Methods, to conducted the manager and workers of Small Scale Industry in Kabupaten Bandung as population target. The sample size was 60 respondents selected randomly based on sampling Random sample, technique. The results of the study showed that: (1) The dynamics of SMSI organization concerning on anatomy, structure, and process organization was effective; (2) the individual on SMSI organization concerning on motivation, attitude, aptitude, temperament, and role perception was effective; (3) The effectivity of marketing communication management on SMSI in Kabupaten Bandung concerning on planning, actuating, controlling, and marketing communication mix was effective; (4) The correlation between the dynamics organization level and individual effectivity on organization SMSI was significan; (5) The correlation between the dynamics organization level and effectivity of marketing communication management on SMSI in Kabupaten Bandung, was significan; and (6) The correlaton between individual effectivity on organization and effectivity of marketing communication managementon SMSI in Kabupaten Bandung was significant.